Responding to New Social Risks. The Southernization of Social Welfare in Poland? - Paweł Poławski (Social Work & Society, 2022)
European welfare states are gradually reorienting toward the activation and social investment paradigm, trying to address changing patterns of social issues and risks. The article asks to what extend welfare policy is modernizing in a sense of reorientation toward new social risks and social investment, and what affects the reorientation processes. It also addresses the question of welfare regimes' typology and hybridization of Central and Eastern European social support system taking Poland as a case, arguing that CEE countries share the elements of the so-called Southern model of the welfare state. The text covers regularities both on the macro level and on the street-level, trying also to answer the question about relations of general policy changes and policy implementation using social assistance as an example. The analysis uses OECD data on social protection as well as qualitative data from 29 in-depth interviews with social workers in six locations in Poland.